Aptameric Probe Specifically Binding Protein Heterodimer Rather Than Monomers. Issue 11 (9th April 2019) - Bing, Tao; Shen, Luyao; Wang, Junyan; Wang, Linlin; Liu, Xiangjun; Zhang, Nan; Xiao, Xiao; Shangguan, Dihua
Abstract: Dimerization of proteins occurs frequently and plays integral roles in biological processes. However, no single molecular probe is available for in situ detection of protein dimers on cells and tissues because of the difficulty of isolating complete protein dimers for probe preparation and screening, which has greatly hampered the biomedical study of protein dimers. Herein, a G‐rich DNA aptamer (termed BG2) that only binds alkaline phosphatase (AP) heterodimers rather than monomers is reported. This aptamer is generated by the cell‐SELEX (systematic evolution of ligands by exponential enrichment) technique and proves to fold into a duplex stabilized antiparallel G‐quadruplex structure. Using BG2 as molecular probe, AP heterodimers are found to be expressed on several kinds of cancer cells. As an affinity ligand, BG2 could isolate AP heterodimers from cell lysate. BG2 is also demonstrated to be applicable for tumor imaging in mice xenografted with cells highly expressing AP heterodimers. AP isozymes are found in several tissues and blood throughout the body, but the function and tissue distribution of AP heterodimers are totally unknown; therefore, BG2 could serve as a molecular probe to uncover the mystery of AP heterodimers. The generation of aptameric probes by cell‐SELEX will open up a new situation for the study of protein dimers. Abstract : A G‐rich DNA aptamer, BG2, generated by cell‐SELEX (systematic evolution of ligands by exponential enrichment), only specifically binds the alkaline phosphatase heterodimer rather than monomers. It can serve as a molecular probe for in situ detection of these heterodimers on cells and in tumors, and as an affinity ligand for the isolation of these heterodimers from cell lysate.